Pengolahan Data Digital Elevation Model Untuk Pembuatan Peta Aliran Debris Pada Sungai Palung Pulau Lombok Provinsi Nusa Tenggara Barat - Noviardi, Noviardi; Qodri, Muhammad Fatih; Rizqi, Al Hussein Flowers (ReTII, 2021)
Debris flow is one type of mass movement that occurs where a combination of loose soil, rock, organic materials, air, and water moves down to a slope. Debris flow usually occurs due to intense surface water flow and heavy rainfall, which erodes and mobilizes loose soil or rock on steep slopes. In the last decade, debris flow disaster have occurred in Lombok Regency which caused many casualties and infrastructure damage. The method used in this modeling is generated from the processing of the Digital Elevation Model (DEM) data which is correlated with several parameters such as volume, friction, etc. Furthermore, the parameters determined are simulated using the RAMMS application. The results of this modeling are numerical data and zonation maps of debris flow prone areas. This Research is expected to be an effort to mitigate debris flow disasters around the Palung watershed, Lombok Regency, West Nusa Tenggara Province. Keyword : debris flow, modeling, RAMMS, Palung Watershed.